The Contrastive Study Between Uslub al-Majhul In Arabic And Uslub Pasiive Voice In English - Wahyuddin, Wahyuddin (Asalibuna, 2020)
The aims of this research are: to know the similarities and differences of uslub al-majhûl in Arabic and uslub passive voice in English, by using a contrastive study analysis. The approach used in this research is descriptive qualitative, the theory used in analyzing the data is Miles and Huberman's theory, namely collecting data, selecting relevant data, presenting data, and concluding. The results of this study are: there are similarities and differences between the two uslubs. The equation is uslub al-majhul is a verb whose subject is discarded and replaced by nâib al-fâ'il, its purpose is to summarize the sentence, the subject is known, the subject is unknown, the subject is afraid, the subject is belittled and the subject is glorified. Uslub passive voice is a verb whose subject is not stated because it is unknown, or because it is vague, or because it is not obligatory to appear in a sentence. Both uslub uses transitive verbs. The difference is that Arabic has many analogies (wazan) to form the verb majhûl, whereas English has only two ways of forming past participles, namely by adding the word "ed" to the root verb and with an indefinite pattern called irregular verbs. In the al-majhûl uslub there is a nâib al-fail that does not have a passive uslub voice. In the uslub of passive voice, it is found that there are modal that are not included in the uslub al-majhûl. Arabic has ismiyah and fi'liah sentences while English only has ismiyah sentences.